Matija Murko in Jan Jakubec v razpravi o češkem narodnem prerodu (pozitivistični koncept literarne zgodovine v korespondenci dveh slovanskih filologov) - Zelenka, Miloš (Primerjalna književnost, 2012)
This article evaluates the positivist concept of literary history as framed by Matija Murko (1861-1952) and Jan Jakubec (1862-1936) in their correspondence concerning the Czech National Revival (Murko: Deutsche Einflüsse...). Both scholars drew on empirical positivism, emphasizing "detached" exposition, which, in contrast to romanticizing nationalistic ideology, recognized German influence on the formation of Slavic culture.
Keywords: Murko, Matija, 1861-1952; Jakubec, Jan, 1862-1936; slovanska filologija; Czech literature; češka književnost; literarna zgodovina; history of literature; narodni prerod; slovanska kultura; empirični pozitivizem